Comparação do esquema de imunossupressão utilizando o mTOR associado ao inibidor de calcineurina com o inibidor de calcineurina isolado na rejeição crônica do enxerto pós-transplante de pulmão - Souza, Andressa Rodrigues de (2019)
The growth of lung transplantation has been constant throughout the world, and with this, the results presented have been progressively better, both in the short and long term. Despite this reality, some problems of difficult solution limit these programs, such as chronic graft rejection and complications secondary to long-term immunosuppression. The immunosuppressive strategies used in lung transplantation are based on triple schemes, composed of a calcineurin inhibitor, an antimetabolic agent and corticosteroids. A fourth group of immunosuppressants consists of inhibitors of cell proliferation, in particular, mTOR inhibitors. In this sense, this review aimed to compare the immunosuppressive regimen based on a calcineurin inhibitor-associated mTOR inhibitor at reduced dose with the calcineurin inhibitor alone in the chronic rejection of the posttransplant lung graft. In order to do so, we applied the methodological design of systematic review of the literature, through searches in electronic health databases (MEDLINE, Wef of Science, Scopus, Cochrane Central, EMBASE and LILACS) and in secondary manual resources. Six scientific articles composed the corpus of analysis for the qualitative synthesis of the results, which referred to three studies named SHITRIT, NOCTET and 4EVERLUNG. The main outcomes were the safety of substitution therapy for calcineurin inhibitor-based immunosuppressive therapy by the treatment of mTOR inhibitor with low patient mortality as well as maintaining efficacy in controlling events of chronic graft rejection. The relevance of the data that indicated an improvement in the renal function of the patients when submitted to the therapy with inhibitor mTOR in relation to calcineurin inhibitors was unanimously highlighted. The studies present a high reliability index due to the manifestation of low risk of bias in most of the items evaluated for the assertive conduction of a randomized clinical trial, in addition to presenting an important recommendation force for clinical decision making. In this sense, this systematic review guides a weighting in the use of mTOR inhibitors, considering the greater risk of mortality in the first year of treatment associated with this therapy. For patients with renal dysfunction associated with the isolated use of calcineurin inhibitors, this review "recommends" a change in the therapeutic regimen for the insertion of mTOR inhibitors into calcineurin inhibitors at a reduced dose, considering the imminent risk of mortality of lung transplant patients under renal insufficiency.